Orwell, politics, and power - Carr, Craig L., 1948- (Continuum, 2010)
Orwell, Politics, and Power takes the political writings in Orwell's literary corpus as a source of inspiration for theorizing about contemporary political issues and themes. By looking at Orwell as a political thinker, the book derives a 'political message' from his works that may qualify as contributions to the liberal political thought. The book argues that Orwell's fears about power becoming its own end resulted from his belief that liberal political culture was under attack by social and economic forces that undermined the foundational beliefs and convictions of liberal political morality.